Medical Students' Progress in Detecting and Interpreting Visual and Auditory Clinical Findings. Issue 4 (7th August 2020) - Han, Heeyoung; Williams, Reed; Hingle, Susan; Klamen, Debra L.; Rull, Gary M.; Clark, Ted; Daniels, James
Abstract: Phenomenon: Detection of visual and auditory clinical findings is part of medical students' core clinical performance abilities that a medical education curriculum should teach, assess, and remediate. However, there is a limited understanding of how students develop these skills. While training physical exam technical skills has received significant attention and emphasis, teaching and assessing medical students' ability to detect and interpret visual and auditory clinical findings skills has been less systematic. Therefore, the purpose of this study is to investigate how medical students' visual and auditory clinical findings skills progress and develop over their four years of undergraduate medical education. This study will provide educators insights that can guide curriculum refinements that lead to improving students' abilities in this area. Approach: A computer-based progress exam was created to measure the longitudinal development of students' abilities to detect and interpret visual and auditory findings. After pilot testing, sixty test items were developed in collaboration with six clinical faculty members and two medical education researchers. The exam includes detection and description of ECG, x-ray, heart sounds, breath sounds, skin lesions, and movement findings. The exam was administered to students at the beginning of each training year since 2014. Additionally, the exam was administered to the Class of 2017 prior to their graduation. Measurement validity and reliability tests were conducted. Descriptive statistics and ANOVA were used to determine progress. Findings: More than 98% of students in four years of training completed the exam each year. The exam instrument had high reliabilities and demonstrated acceptable concurrent validity when compared with other academic performance data. Findings showed that students' visual and auditory clinical findings skills increased each training year until their fourth year. There was no performance improvement between incoming Year 4 students and graduating Year 4 students. While group means increased, class performance did not become more homogeneous across four years. Longitudinal data showed the same performance patterns as the cross-sectional data. Performance of the bottom quartile of graduating fourth-year students was not significantly higher than the performance of the top quartile of incoming first-year students who had not had formal medical training. Insights: A longitudinal study to follow learners' performance in detecting and interpreting visual and auditory clinical findings can provide meaningful insights regarding the effects of medical training programs on performance growth. The present study suggests that our medical curriculum is not effective in bringing all students to a higher level of performance in detecting and interpreting visual and auditory clinical findings. This study calls for further investigation how medical students can develop visual and auditory detection and interpretation skills in undergraduate medical education. There is a need for planned curriculum and assessment of medical students' skills in detecting and interpreting visual and auditory clinical findings.